Odpowiedzi

2010-02-12T15:38:13+01:00
1.
a.4x-5y+7x-3y= 11x - 8y
b.11x-11y-23x-45y-7= - 12x - 56y -7
c.3x-4+5x+9-11= 8x - 15 + 5x
d.7x+7y-10-5x-10y= 2x - 3y - 10

2.
a.3(x-2y+4)= 3x - 6y +12
b.5(3x-3y-7)= 15x - 15y - 35
c.6(4x=2y)= 24x + 12y
d.2(3x-4y)= 6x - 8y
2010-02-12T15:41:09+01:00
1.Wykonaj redukcje wyrazow podobnych
a.4x-5y+7x-3y=
=11x -8y

b.11x-11y-23x-45y-7=
= -12x -56y -7

c.3x-4+5x+9-11=
= 8x -6

d.7x+7y-10-5x-10y=
= 2x -3y -10

2.Wykonaj mnożenie
a.3(x-2y+4)=
= 3x +3*(-2y) + 3*4=
= 3x -6y +12

b.5(3x-3y-7)=
= 5*3x +5*(-3y) + 5*(-7) =
= 15x -15y - 35

c.6(4x=2y)= przypuszczam,że w nawiasie ma być + zamiast =
= 6*4x + 6*2y =
=24x + 12y

d.2(3x-4y)=
= 2*3x +2*(-4y) =
=6x - 8y
2010-02-12T15:43:57+01:00
1.
4x+7x-3y-5y=11x-8y
11x-23x-45y-7-11y=-12x-56y-7
3x+5x+9-11-4=8x+9-15=8x-6
7x-5x-10y+7y-10=2x-3y-10
2.
3x(x-2y+4)=3x kwar.-6xy+12x
5(3x-3y-7)=15x-15y-35
6(4x-2y)=24x-12y
6(4x+2y)=24x+12y
6(4x=2y)=24x=12y
2(3x-4y)=6x-8y